Final answer:
To solve the equation 6t-2/3+t/5=4+2-t/3, we need to simplify and rearrange the equation to isolate the variable t. The solution is t = 80/98.
Step-by-step explanation:
To solve the equation 6t-2/3+t/5=4+2-t/3, we need to simplify and rearrange the equation to isolate the variable t. First, let's get rid of the fractions by multiplying every term in the equation by 15 (the least common multiple of 3 and 5). This gives us 90t - 10 + 3t = 60 + 30 - 5t. Combining like terms, we have 93t - 10 = 90 - 5t. To further simplify, let's move all the t terms to one side of the equation by adding 5t to both sides, giving us 98t - 10 = 90.
Next, we can isolate t by subtracting 10 from both sides of the equation, resulting in 98t = 80. Finally, divide both sides of the equation by 98 to solve for t, giving us t = 80/98.